Insertion of the dorsal oblique muscle in the dog: an anatomic basis for ventral strabismus associated with oculomotor nerve dysfunction. (3rd January 2013) - O'Neill, Jeremy J.; Kent, Marc; Glass, Eric N.; Platt, Simon R.; de Lahunta, Alexander
Abstract: Objective: To describe the insertion of the dorsal oblique (DO) muscle in relationship to the equator of the globe in dogs. Procedure: The study was conducted on 10 fresh cadaver eyes from five dogs, which were euthanized for disease processes unrelated to ocular disease. A manual vernier caliper was used to determine the calculated measurements. Results: The median anterior‐to‐posterior diameter of the globe was 21 mm. The median length from the vertex of the anterior pole to the anterior point of insertion of the DO tendon was 11.5 mm. The median length from the posterior pole to the posterior point of insertion of the DO tendon was 10 mm. The width of tendon of insertion of the DO tendon was 3.25 mm. Conclusions: In disorders involving the oculomotor nerve or the oculomotor nerve nucleus in the mesencephalon, the resultant strabismus is directed ventrolaterally. Based on the insertion of the superior oblique muscle in humans, we hypothesized that the DO muscle would likely explain the ventral deviation in disorders of the oculomotor nerve or its nucleus. In this study, the point of the insertion of the DO muscle tendon was posterior to the equator. Based on this anatomic location, unopposed function of the DO muscle would be expected to result in ventral deviation of the globe.